Friday

July 25, 2014

July 25, 2014

Posted by **sonia** on Tuesday, April 1, 2008 at 10:38am.

prove that

(1+sinA+icosA)/(1-sinA-icosA)=i(secA+tanA)

- algebra -
**Reiny**, Tuesday, April 1, 2008 at 1:50pmmultiply the left side by (1-sinA+icosA)/(1-sinA+icosA)

expand and simply it down to

icosA/(1+sinA)

multiply that by (1-sinA)/(1-sinA)

expand again and simplify down to

i(1-sinA)/cosA

= i(1/cosA - sinA/cosA)

= i(secA - tanA)

= Right Side

**Related Questions**

Trig - Please help with this one. I've worked it out in so many ways and can't ...

Maths - Hi, can someone give me the answer to this question: secA-tanA=1/4. Find...

maths(trigonometry) - prove that sinA-cosA+1/sinA+cosA-1=1/secA-tanA

Trig - prove that tanA divided by the sinA equals the secA

mathematics trignometry - prove that the following are identity 1. (cotA+cosecA-...

math - (secA+tanA)(1-sinA)

Math - In any angle ABC prove tht the perimeter = a/Sin A(Sin A + Sin B + Sin C...

maths - prove that secA(1-sinA)-2tanA=1

trig - express the trig. ratios sinA,secA n tanA in terms of cotA.

MathS triG - 1 .If tanA=1/3 and tanB=1/7 (both A and B are acute),calculate ...